Radiography with neutrons [proceedings of a] conference held 10-11 September, 1973 at the University of Birmingham - Hawkesworth, Michael Rowling (British Nuclear Energy Society, 1975)
Proceedings of a conference held at University of Birmingham on 10-11 September 1973.